The History and Present of Mamun Academy - Juraev Hamza Atoevich (International Journal Of History And Political Sciences, 2025)
The article provides extensive information on the history of the scientific academy founded in the land of Khorezm during the difficult socio-political situation in the region of Maverannahr, and on the basis of evidence it is proved that Shah Mamun was one of the most outstanding rulers of the Middle Ages in patronage of science and culture, which is now recognized by the entire enlightened world, that after a thousand years historical justice was established, and that this position undoubtedly had great significance in the restoration and development of Uzbek statehood, Uzbek science and education. In particular, based on scientific data, the history of the 164th specialized lyceum and boarding school of the Karakul district of the Bukhara region, the pedagogical activities of the winners of republican and world Olympiads are covered.